2016
DOI: 10.1007/s12185-016-2026-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for primary breast lymphoma in male gynecomastia: a rare case report and review of the literature

Abstract: Primary breast lymphoma is a rare type of non-Hodgkin lymphoma and usually affects women, although a few cases have been reported in men. Chemotherapy and radiation therapy, or a combination of both, are frequently administered for treatment of primary breast lymphoma, as local control by surgical resection is poor. No standard therapy has been established, and the optimal radiation dose and irradiation field for male patients are unknown. The present report describes a 75-year-old man with bilateral cirrhosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The details of histological subclassifications of female and male patients are listed in Supplementary Tables 3 and 4 , respectively. For both genders, consistent with the previous study ( 13 ), diffuse large B-cell lymphoma was the most common type, followed by extranodal marginal zone lymphoma (mucosa-associated lymphoid tissue type) and follicular lymphoma. Thus, we hypothesize that male PBL patients may be similar to females in terms of clinical demographics.…”
Section: Discussionsupporting
confidence: 91%
“…The details of histological subclassifications of female and male patients are listed in Supplementary Tables 3 and 4 , respectively. For both genders, consistent with the previous study ( 13 ), diffuse large B-cell lymphoma was the most common type, followed by extranodal marginal zone lymphoma (mucosa-associated lymphoid tissue type) and follicular lymphoma. Thus, we hypothesize that male PBL patients may be similar to females in terms of clinical demographics.…”
Section: Discussionsupporting
confidence: 91%
“…Bsymptoms (systemic symptoms associated with Hodgkin and nonHodgkin lymphoma) such as fever, weight loss, and night sweats are common in SBL and are rare in PBL, potentially owing to the presence of advanced extramammary lymphoma in SBL (26)(27)(28)(29). While breast lymphoma occurs almost exclusively in women, case reports have been published docu menting the exceedingly rare diagnosis of both PBL and SBL in men (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies had no English full text, so data was limited to the abstracts [8,9]. The data of 5 cases were extracted from one study which was a case report and review article [10] and the review part of this study included data of 4 cases whose original articles (case reports) were not found.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly in the present review, all eight male patients who received radiotherapy combined with other treatment modality were alive without evidence of disease after a median of 17 months [10,[24][25][26][27][28]. Four patients received higher than 30 Gy (they mostly received 50 Gy), and information about radiation dosage was not available in one patient [24].…”
Section: Treatmentmentioning
confidence: 97%